Create your research poster - Lacatus, Corina; Nogues, Alex (Super quick skills, 2021)
Need to design a research poster but not sure where to start? This book breaks down everything you need to know about translating your research project into an effective research poster. Learn the basic elements of good poster design Ensure your poster captures all the relevant aspects of your research Understand how to tell a story with your poster Succeed at university with Super Quick Skills - giving you the tools and advice you need to quickly progress your skills, and excel in your studies and life. Find out more at sagepub.co.uk/sqs"--